Translocation of pharmaceuticals from wastewater into beehives. (January 2020) - Carter, Laura J.; Agatz, Annika; Kumar, Anu; Williams, Mike
Graphical abstract: Highlights: Pharmaceuticals can accumulate in nectar and pollen of flowering plants. Honeybees can be exposed to pharmaceuticals, commonly present in wastewater. Pharmaceutical accumulation in beehives depends on seasonal and locational factors. More work is urgently need to explore potential implications for honeybee health. Abstract: There has been a substantial research focus on the presence of pesticides in flowers and the subsequent exposure to honeybees. Here we demonstrate for the first time that honeybees can also be exposed to pharmaceuticals, commonly present in wastewater. Residues of carbamazepine (an anti-epileptic drug) up to 371 ng/mL and 30 µg/g were detected in nectar and pollen sampled from zucchini flowers ( Cucurbita pepo ) grown in carbamazepine spiked soil (0.5–20 µg/g). Under realistic exposure conditions from the use of recycled wastewater, carbamazepine concentrations were estimated to be 0.37 ng/L and 30 ng/kg in nectar and pollen, respectively. Incorporation of environmentally relevant carbamazepine residues in nectar and pollen into a modelling framework able to simulate beehive dynamics including the honeybee foraging activity at the landscape scale (BEEHAVE and BEESCOUT) enabled the simulation of carbamazepine translocation from zucchini fields into honeybee hives. Carbamazepine accumulation was modelled in 11 beehives across a 25 km 2 landscape over three years chosen to represent distinct climatic conditions. During a single flowering period, carbamazepine concentrations were simulated to range between 0 and 2478 ng per beehive. The amount of carbamazepine gathered not only varied across the simulated years but there were also differences in accumulation of carbamazepine between beehives within the same year. This work illustrates a fundamental first step in assessing the risk of pharmaceuticals to bees through realistic scenarios by demonstrating a method to quantify potential exposure of honeybees at the landscape scale. Pharmaceuticals are being inadvertently but increasingly applied to agricultural lands globally via the use of wastewater for agricultural irrigation in response to water scarcity problems. We have demonstrated a route of pharmaceutical exposure to honeybees via contaminated nectar and pollen. Given the biological potency of pharmaceuticals, accumulation of these chemicals in nectar and pollen suggest potential implications for honeybee health, with unknown ecosystem consequences.